Cryoballoon ablation beyond pulmonary vein isolation in the setting of persistent atrial fibrillation. (4th May 2022) - Miraglia, Vincenzo; Bisignani, Antonio; Pannone, Luigi; Iacopino, Saverio; Chierchia, Gian-Battista; de Asmundis, Carlo
ABSTRACT: Introduction: Catheter ablation has been demonstrated to be a safe and an effective treatment for drug resistant atrial fibrillation (AF); electrical isolation of pulmonary veins (PVI) is the main strategy in paroxysmal AF, since pulmonary vein triggers have a pivotal role in its pathogenesis; non-paroxysmal AF is a complex arrhythmia that results from the interplay of a substrate, namely AF-induced electrical and structural atrial remodeling, and a trigger that can be often found outside pulmonary veins, namely non-pulmonary veins triggers. Areas covered: The aim of this review is to provide a state-of-the-art overview of non-pulmonary veins triggers with special focus on cryoballoon (CB) catheter ablation. Expert opinion: Besides PVI, CB catheter ablation of non-pulmonary veins triggers is a novel and promising strategy for non-paroxysmal AF.